2018
DOI: 10.1097/nmd.0000000000000727
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Negative Life Events on Attempted Suicide in Rural China

Abstract: This study aims to explore the impact of negative life events (NLEs) on attempted suicide in a Chinese cultural setting. The sample comprised 791 suicide attempters and an equal number of controls matched on age, sex, and location from selected rural counties in China. Conditional logistic regression model was used to examine the association between NLEs and suicide risk. The impact of NLEs on attempted suicide was further examined using regression-based method to explore its mediation effect. The types of NLE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 41 publications
2
11
1
Order By: Relevance
“…A study by Liu and Zhang showed love/marriage shambled down in 52.3% poorly adjusted and 4.9% dissatisfied couples, insofar as each of such digressions are weighted as individual negative life events. 53 In contrast, the marital adjustment scores were relatively higher in the love marriage group in this study, perhaps from the prior sensitization to the partner's pattern of likings, attitudes, behavior and lifestyle. Couple satisfaction was found to have moderate positive correlation with impulsiveness in both groups, which could be speculated to be due to the effect of promptness of positive emotional responses and pleasing reciprocations contributing to the satisfaction scores.…”
Section: Discussioncontrasting
confidence: 67%
See 1 more Smart Citation
“…A study by Liu and Zhang showed love/marriage shambled down in 52.3% poorly adjusted and 4.9% dissatisfied couples, insofar as each of such digressions are weighted as individual negative life events. 53 In contrast, the marital adjustment scores were relatively higher in the love marriage group in this study, perhaps from the prior sensitization to the partner's pattern of likings, attitudes, behavior and lifestyle. Couple satisfaction was found to have moderate positive correlation with impulsiveness in both groups, which could be speculated to be due to the effect of promptness of positive emotional responses and pleasing reciprocations contributing to the satisfaction scores.…”
Section: Discussioncontrasting
confidence: 67%
“…41 About 75.6% of suicide attempters had experienced at least one negative life event, and events were significantly correlated with attempted suicide in married/love partners. 53 The association of impulsivity expressed as the imprudent, illadvised and reckless ideation in the face of marital disharmony among attempters is a significant factor in Indian 54 and other Asian studies. 3 While high intent was seen in the arranged group than the love group in our study, Sarkar et al found in his study on attempters and selfharmers, in the former, the acts were thoughtful, intent and fatality was high, with less voluntary disclosure; the latter were emotionally unstable with personality difficulties, with impulsive, low intent and less lethal attempts, and most seeking rescue eventually.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have shown that the effect of stressful event on suicide may be directly or indirectly modulate by MDD. [ 19 20 27 ]…”
Section: Discussionmentioning
confidence: 99%
“…Negative life events are significantly associated with an increased risk for suicide . It is important to have a valid scale to measure the predictive indicator of life events in suicide prevention.…”
Section: Discussionmentioning
confidence: 99%